2001
DOI: 10.1109/83.913596
|View full text |Cite
|
Sign up to set email alerts
|

Feature-enhanced synthetic aperture radar image formation based on nonquadratic regularization

Abstract: We develop a method for the formation of spotlight-mode synthetic aperture radar (SAR) images with enhanced features. The approach is based on a regularized reconstruction of the scattering field which combines a tomographic model of the SAR observation process with prior information regarding the nature of the features of interest. Compared to conventional SAR techniques, the method we propose produces images with increased resolution, reduced sidelobes, reduced speckle and easier-to-segment regions. Our tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
284
0
12

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 498 publications
(299 citation statements)
references
References 37 publications
(70 reference statements)
3
284
0
12
Order By: Relevance
“…In order to avoid problems due to non-differentiability of the l 1 -norm [31], a smooth approximation to the l 1 -norm is used in (3):…”
Section: Scattering Centers Features Extraction With Sparse Constraintmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to avoid problems due to non-differentiability of the l 1 -norm [31], a smooth approximation to the l 1 -norm is used in (3):…”
Section: Scattering Centers Features Extraction With Sparse Constraintmentioning
confidence: 99%
“…To solve the problem of Equation (5), we adopt the quasi-Newton method in [31] which can account for the complex-valued nature of the SAR problem. The solution procedure is briefly described here.…”
Section: Scattering Centers Features Extraction With Sparse Constraintmentioning
confidence: 99%
“…Using an exhaustive search, the restoration, given in (2) with side constraint (5), is computed for all λ values within the interval [a, b]. At the end of each restoration, the kurtosis is used to determine the quality of the reconstructed image,f (λ).…”
Section: A Image Quality Measurementioning
confidence: 99%
“…Cetin and Karl [5] suggested that the side constraint function, ||f || p p with p ≤ 1, enhances point-based features and improves the resolvability of objects when there is a small number of dominant scatterers in the scene. In comparison, the function, ||∇f || p p with p ≈ 1, enhances region-based shape features that are useful for segmenting the object, shadow and background regions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation